2022
DOI: 10.1007/s11064-022-03682-1
|View full text |Cite
|
Sign up to set email alerts
|

Advances in construction and modeling of functional neural circuits in vitro

Abstract: Over the years, techniques have been developed to culture and assemble neurons, which brought us closer to creating neuronal circuits that functionally and structurally mimic parts of the brain. Starting with primary culture of neurons, preparations of neuronal culture have advanced substantially. Development of stem cell research and brain organoids has opened a new path for generating three-dimensional human neural circuits. Along with the progress in biology, engineering technologies advanced and paved the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 136 publications
0
2
0
Order By: Relevance
“…For a single cell after subcellular chemical damage, the tentacle would lose its viability (shown by the calcein-AM test) without shrinkage or regeneration, while the cell body would heal its wound and regenerate (Figure e), which indicated that the nucleus might be essential for the survival, wound healing, and regeneration of neural cell fragments. These results showed that our design is an effective method for in situ subcellular stimulation, which could be potentially combined with neural models and chemical analysis (e.g., subcellular mass spectrometry or microsensors) to promote neurology research.…”
Section: Results and Discussionmentioning
confidence: 87%
“…For a single cell after subcellular chemical damage, the tentacle would lose its viability (shown by the calcein-AM test) without shrinkage or regeneration, while the cell body would heal its wound and regenerate (Figure e), which indicated that the nucleus might be essential for the survival, wound healing, and regeneration of neural cell fragments. These results showed that our design is an effective method for in situ subcellular stimulation, which could be potentially combined with neural models and chemical analysis (e.g., subcellular mass spectrometry or microsensors) to promote neurology research.…”
Section: Results and Discussionmentioning
confidence: 87%
“…Several other works stemmed from this original study [ 21 ] to explore some fundamental (and critical) steps for the development of neuromorphic neuroprostheses. The main elements of innovation are related to different types of communication modalities [ 56 ] by taking advantage of the latest technological developments [ 57 , 58 , 59 ] or increasing the complexity of the experimental model [ 60 ]: all the above comes with additional opportunities and challenges, as presented in the following sections.…”
Section: Neuromorphic Neuroprostheses: State-of-the-art and Perspectivesmentioning
confidence: 99%